Análise de caracteres morfológicos e comportamentais em abelhas africanizadas, caucasianas e em descendentes dos seus cruzamentos - Malaspina, Osmar [UNESP]; Stort, Antonio Carlos [UNESP]; Bueno, Odair Correa [UNESP] (Sociedade Brasileira de Zoologia, 1989)
Twetve external morphological traits and seven traits of food-gathering behavior were studied in africanized and caucasian (A. m. caucasica), bees. Discriminant analysis showed that neither the length of the fourth segment of the abdomen, nor bee weight can be considered as the traits with the highest discriminatory power between africanized and caucasian bees, with any in-bred bees. In the case of in-bred bees the discriminam traits had a lower interorbital width and time to reach the feeder. Multivariate comparisons between the data of in-bred colonies and twenty hibrid colonies, suggest dominance of the genes group of the africanized subspecies.